The truths and lies of nationalism ; as narrated by Charvak - Chatterjee, Partha, 1947- (SUNY Press, 2022)
Rejects Hindu nationalism and pluralist secularism in favor of a revitalized politics of Indian federalism.
Keywords: Cārvāka.; Cārvāka; Nationalism -- India -- History.; Democracy -- India.; Hindutva.; India -- Politics and government.; Inde -- Politique et gouvernement.; Intégrisme hindou.; HISTORY / Asia / South / General; Hindutva; Democracy; Nationalism; Politics and government; India; History